EVALUATION OF ELECTRONIC MEDICAL RECORD DOWNTIME AT MRCCC SILOAM SEMANGGI CANCER HOSPITAL USING EMRAM AND ISO 22301 FRAMEWORK - Anom Suseno; Pipit Dewi Arnesia (Jurnal Indonesia Sosial Teknologi, 2025)
Downtime is a term to describe a condition where a computer or information system is offline or not operating, processes that must occur in information systems, both on schedule and at unwanted times. The electronic medical record system at MRCCC Siloam Hospital Semanggi experienced downtime at unwanted times more than twice with a relat4ely long time which resulted in disruption of health services to patients and decreased business revenue. The quality of electronic medical records at the MRCCC Siloam Hospital Semanggi and service readiness when system downtime occurs, are known using The Electronic Medical Record Adoption Model (EMRAM) standard method and ISO 22301 Framework. Direct observation or observation using the ISO 22301 Framework standard reference. Questionnaires circulated to general practitioners as users of electronic medical records using questions that refer to EMRAM standards. The readiness of MRCCC Siloam Hospital Semanggi in dealing with electronic medical record downtime reached 83 percent capable when serving patients. The questionnaire distributed has met the criteria of correlation and significance so that it is considered valid for all questions and has met the criteria of Cronbach's Alpha score which states Reliable.